The effects of inulin and polydextrose fortifications on physicochemical properties, probiotic viability and sensory acceptability of coconut milk set yoghurt analogue - Pattawee, N.; Sriprom, P.; Siriwongwilaichat, P. (My University, 2026)
Although inulin and polydextrose are widely used as prebiotics to improve the quality and the nutritional properties of food products, their functionality, and optimal levels in coconut milk set yoghurt analogue remain poorly understood due to the fundamentally different matrix compared to dairy yoghurt. The objective of this study was to investigate the effect of inulin and polydextrose fortification on the quality attributes of coconut milk set yoghurt analogues (CYA). Each prebiotic was varied at 1, 3, 5, and 7% (w/v) with a non-prebiotic sample serving as a control. The properties of CYA were then evaluated for pH, titratable acidity, syneresis, and water-holding capacity, firmness, microstructural properties, rheological properties, and sensory acceptability. It was found that the firmness, syneresis, and water-holding capacity of CYA significantly increased with increasing levels of either inulin or polydextrose (p ≤ 0.05). In addition, increasing prebiotics resulted in increasing storage modulus (G՛) and loss modulus (G՛՛). Microstructure observation indicated a finer gel network in CYA fortified with increasing prebiotic up to 5% (w/v). The addition of prebiotics resulted in a considerable increase in viable probiotic counts compared with the control yoghurt. According to sensory evaluation, a significantly improved score (7.41–7.42) was observed in CYA fortified with polydextrose at all concentrations (p ≤ 0.05), whilst that fortified with 5% (w/v) inulin gave the best result. This study demonstrated that inulin and polydextrose can function effectively as structure-forming and functional ingredients in coconut milk set yoghurt analogue, and identifies suitable concentration ranges for improving physicochemical, rheological, microstructural, probiotic, and sensory properties. These findings extend the application of prebiotics to plant-based yoghurt systems and provide practical guidance for the development of high-quality functional non-dairy yoghurt products.
Keywords: Microstructure; Non-dairy alternative; Plant-based yoghurt; Prebiotic; Rheology